The politics of administration: a study of the career of Dr D L Smit with special reference to his work in the Department of Native Affairs, 1934-1945 - Bell, M M S (Rhodes University, Faculty of Humanities, Department of History, 1978)
The written history of modern South Africa is limited by the moratorium on archival material common to' all contemporary research, and the present study is intended, in part, to help fill this gap. It has a two- fold design: first, to point out some of the anomalies in the relationship between administration and policy and secondly, to show the extent to which they are interdependent in Dr. D.L. Smit ' s career. In the process, I hope to clarify and to comment on some of the mechanics involved in Native Administration.
Keywords: Smit, Douglas Lainge; 1885-; South Africa. Native Affairs Commission; South Africa -- Native Affairs Department; South Africa -- History -- 1909-1961